KADAR HAEMOGLOBIN PADA PEROKOK DAN BUKAN PEROKOK - Aktalina, Lucia; Mayzar, Dwi Ilham (Majalah Ilmiah METHODA, 2023)
The number of smokers in Indonesia is increasing every year, thereby increasing the risk factors for various diseases such as: cardiovascular, respiratory, hematological, vascular and malignancy. One of the blood components that has an impact as a result of smoking is Hemoglobin (Hb). Cigarettes produce many chemical compounds that are not good for the body, one of which is carbon dioxide. The high carbon dioxide will cause the affinity for oxygen and Hb to decrease, causing hypoxia. Hypoxia will affect Hb synthesis in the body. The design of this study was cross-sectional with a sample size of 55 people selected according to inclusion and exclusion criteria and divided into two groups. 28 people consisted of smokers and 27 non-smokers in the Mekarjaya area, Subang, West Java. This area is a lowland area so that it affects the Hb levels of the people around it. The lower a place to eat, the higher the partial pressure of oxygen. This dermographic factor is one of the factors causing the low respondent's Hb level. In addition, most of the respondent professions in this study were farmers who had heavy physical activity. Physical activity also affects a person's Hb levels. As many as 63.6% of respondents had low Hb levels, 34.5% had normal Hb levels and 1.9% had high Hb levels. There is a difference in Hb carbs between smokers and non-smokers with a p value <0.005.